An exploratory investigation: are driving simulators appropriate to teach pre‐driving skills to young adults with intellectual disabilities?. (30th April 2013) - Brooks, Johnell O.; Mossey, Mary E.; Tyler, Peg; Collins, James C.
<x xml:space="preserve">Abstract</x> Accessible summary There were many driving education studies with adults with intellectual disabilities (ID) in the 1960s and 1970s, but since, very little research has been carried out. This study explored using an interactive driving simulator for teaching adults with intellectual disabilities to learn pre‐driving skills (lane keeping and speed maintenance). The simulator succeeded in rapid identification of the drivers' capabilities and limitations, providing skill practise that would be unsafe on roadways, creating a fun, effective and flexible learning environment and highlighting the most appropriate areas for future research. Summary Research examining driver training for young adults with intellectual disabilities has been limited since the 1970s. The current pilot and exploratory study investigated teaching pre‐driving skills (i.e. lane keeping and speed maintenance) to young adults with intellectual disabilities using an interactive driving simulator to provide dynamic and immediate feedback to participants as well as quantifiable data to researchers and educators. Four students from a post‐secondary transition course for students with intellectual disabilities (age 21–23) with an average full‐scale IQ of 71.5 (range 64–76) participated. Participants practised their pre‐driving skills (lane keeping and speed maintenance rather than complex driving environments) on a series of driving courses as well as a coordinated muscle movement activity related to driving for 1 h a day, 5 days a week. After 27 days, two of the four participants significantly improved their lane keeping and speed maintenance skills, while two participants failed to demonstrate steady improvement.